Strategic Assessment of BSI Smart Agents: A SWOT Approach to Promoting Financial Inclusion in Cirebon Indonesia - Yudian, Inge; Nakhwatunnisa, Haulah; Aziz, Abdul (Jeksyah: Islamic Economics Journal, 2025)
This study analyzes the BSI Smart Laku Pandai program in Cirebon using a SWOT analysis approach, aiming to evaluate the potential and challenges faced by agents in implementing inclusive financial services. The study identifies four types of strategies based on the results of the SWOT matrix, namely SO (Strength-Opportunities), WO (Weaknesses-Opportunities), ST (Strengths-Threats), and WT (Weaknesses-Threats) strategies. The SO strategy focuses on leveraging the strengths of simple and guaranteed products to attract additional income opportunities for agents. The WO strategy seeks to address weaknesses in resources and technology by adding staff and improving service application performance. The ST strategy aims to mitigate external threats by strengthening the relationship between the bank and agents through supervision and education. Lastly, the WT strategy reduces weaknesses and avoids threats by ensuring the availability of services such as savings books and ATM cards, as well as conducting regular surveys of agents. This study provides recommendations for developing and maintaining the quality of Laku Pandai services by strengthening the role of agents at the local level and improving financial and technological literacy within the community. It is hoped that this research can serve as a reference for improving inclusive finance policies in Cirebon and other regions.